A fault tolerant algorithm for integrated coverage and connectivity in wireless sensor networks. (25th August 2021) - Ansari, Nishat Afshan; Deshpande, Umesh Ashok; Mohammad, Sahista Parveen
There are two major requirements for any surveillance application using wireless sensor networks (WSN) - coverage and connectivity. In the design of such an application, a major constraint is limited battery life time of the sensor nodes. Due to depletion of battery, sensor nodes might fail and it is very important that the application should be fault tolerant so that events can be reported even in case of failure of a few nodes. In this paper, we propose a fault tolerant algorithm for integrated coverage and connectivity, named FTICC. FTICC does not require clock synchronisation of nodes or the exact location information of the nodes. Through extensive simulation experiments, we have shown that FTICC achieves a better lifetime and data packet delivery ratio (DPDR) as compared to other algorithms. It achieves the maximum DPDR of 1 for a large duration of the network lifetime even in the presence of node failures.